Cancer‐associated venous thromboembolism in Israel: Incidence, risk factors, treatment, and health care utilization in a population based cohort study. Issue 4 (23rd May 2022) - Sharman Moser, Sarah; Spectre, Galia; Raanani, Pia; Friedman‐Mazursky, Orr; Tirosh, Matanya; Chodick, Gabriel; Leader, Avi
Abstract: Background: Recent international guidelines recommend thromboprophylaxis in patients with cancer at intermediate‐high venous thromboembolism (VTE) risk. Objectives: We aimed to assess the current incidence, risk factors and management of cancer‐associated VTE and associated health care resource utilization in a 2.5‐million‐member state‐mandated health service in Israel. Methods: Patients aged ≥18 years with newly diagnosed cancer, initiating systemic anticancer treatment from 2010 through 2018 were identified from the Israel National Cancer Registry. The index date was fixed as the first day of systemic anticancer treatment. The cumulative VTE incidence from the first day of systemic anticancer treatment and the respective hazard ratios for VTE risk factors were calculated at 12 months of follow‐up. Health care resource utilization (primary care physician, emergency room, and hospital visits) during the study period was compared between patients with and without VTE. Results: A total of 15 388 patients were included, and 338 had VTE with a 12‐month cumulative incidence of 2.2% (95% confidence interval, 1.96%‐2.43%). In a multivariable model, older age, higher comorbidity index, intermediate‐high‐risk Khorana score, certain malignancy types, and chemotherapy were significantly associated with an increased VTE risk in the year after initiating anticancer treatment. Compared with matched controls, the VTE subcohort were more likely to be hospitalized (81.4% vs 35.2%), have longer hospital stays (20.1 days vs 13.1 days), have an emergency room visit (41.5% vs 19.3%), and have a larger number of primary care physician visits (17.6 vs 12.5). Conclusion: Several risk factors, including the Khorana score, were associated with VTE incidence. VTE was associated with long‐term use of anticoagulation. Health care utilization was higher in patients with VTE.